Critical Discourse Analysis of Colonial Oppression Richard Wagamese’s Indian Horse and Michelle Good’s Five Little Indians - Muhammad, Kashif; Khan, Bilal; Ilyas, Muhammad (Annals of Human and Social Sciences, 2024)
The aim of this paper is to provide a postcolonial reading of Richard Wagamese ’s Indian Horse and Michelle Good’s Five Little Indians using critical discourse analysis as a framework. Both works of fiction focus on the violent history of the Canadian residential schools which attempted to strip the indigenous children off their culture and abuse them in other ways. By applying a CDA approach, this research explores how the writers have presented the discursive processes of colonization, cultural genocide and the prevailing cycles of trauma amongst native people. The study is qualitative in nature where the text of the novels has been analyzed through the three dimensional model of CDA presented by Fairclough. The study shows various ways in which the native people have faced colonial oppression as depicted in the selected novels. The study recommends to explore the the novels through the theoretical prespectives of psychoanalysis.